Design and Implementation of Tangerang Regency Korpri and Cooperative E-Commerce Service Applications (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2024)
Public services and cooperatives play a crucial role in the local economy. The Koperasi Korpri in Tangerang Regency faces challenges in providing efficient and effective access to its members due to the cooperative building's location, which is not always easily accessible. With advancements in information technology, there is an urgent need to modernize the way services are provided, especially through digital solutions. This project aims to design and implement a service application for Korpri and e-commerce for the Tangerang Regency Cooperative. The goal is to enable Korpri members to access cooperative services without physical location constraints, enhance the efficiency and transparency of transactions, and provide a platform that can be accessed via mobile devices. The project uses the SDLC (Software Development Life Cycle) methodology, which consists of five main stages: planning, analysis, design, implementation, and maintenance. Each stage includes various activities such as requirements identification, UI/UX design, frontend and backend development, application testing, and deployment. It is expected that the resulting application will address geographical challenges and improve the cooperative's operational efficiency. This application is anticipated to enhance transparency and member trust through easily accessible transaction records and provide an intuitive and user-friendly interface. Additionally, the application is expected to strengthen the cooperative's digital infrastructure, support local economic growth, and improve the welfare of cooperative members.